Identification of protective biologic factors in patients with high cardiovascular risk, but normal coronary arteries (NormCorn). Issue 7 (22nd July 2022) - Shaked, Einat; Shaul, Aviv A.; Perl, Leor; Leshem- Lev, Dorit; Sevilya, Ziv; Kheifets, Mark; Gutstein, Ariel; Hamdan, Ashraf; Kornowski, Ran; Lev, Eli I.
Abstract : Background: Endothelial progenitor cells (EPCs) have an important role in repair following vascular injury. Telomere length has been shown to be correlated with genome stability and overall cell health. We hypothesized that both EPCs and telomere size are related to protective mechanisms against coronary artery disease. Our aim was to evaluate the level and function of circulating EPCs and telomere length in patients with multiple cardiovascular risk factors and anatomically normal coronary arteries vs. matched controls. Methods: We included 24 patients, with coronary CTA demonstrating normal coronaries and a high risk of CAD of >10% by ASCVD risk estimator. Control groups included 17 patients with similar cardiovascular profiles but with established CAD and a group of 20 healthy volunteers. Circulating EPCs levels were assessed by flow cytometry for expression of vascular endothelial growth factor receptor 2, CD34 and CD133. The capacity of the cells to form colony forming units (CFUs) was quantified after 1 week of culture. Telomere length was determined by the southern blotting technique. Results: Patients with high risk for CVD and normal coronaries had augmented EPCs function, compared with the CAD group (1.1 vs. 0.22 CFU/f; P  = 0.04) and longer telomeres compared with the CAD group (10.7 kb vs. 2.8 kb P  = 0.015). These patients displayed a similar profile to the healthy group. Conclusion: Patients with a high risk for CAD, but normal coronary arteries have EPCs function and telomere length which resemble healthy volunteers, and augmented compared with patients with established CAD, which could serve as a protective mechanism against atherosclerosis development in these high-risk patients.